Relationship between glycemic control and cognitive impairment: A systematic review and meta-analysis - Lin, Yufeng; Gong, Zhongying; Ma, Chunchao; Wang, Zhiyun; Wang, Kaiyuan (Frontiers in Aging Neuroscience, 2023)
Background: Diabetes mellitus, or hyperglycemia, is an independent risk factor for cognitive impairment. Here we systematically analyzed whether glycemic control could improve cognitive impairment in patients with diabetes mellitus (DM), hyperglycemia, or insulin resistance. Methods: Three databases (PubMed, EMBASE, and Cochrane Library) and Clinical Trials.gov were searched for randomized controlled trials analyzing the relationship between glycemic control and cognitive function assessments, published from database inception to June 2022. Patients in experimental groups were treated with antidiabetic drugs, while control groups were treated with a placebo or alternative antidiabetic drugs. Data analysis was conducted using RevMan 5.3 and StataSE-64, and standardized mean difference (SMD) and 95% confidence intervals (CIs) were calculated. Results: Thirteen studies comprising 19,314 participants were included. Analysis revealed that glycemic control significantly attenuated the degree of decline in cognitive function assessment scores (SMD=0.15; 95% CI 0.05, 0.26; p<0.00001), and funnel plots confirmed no publication bias. Seven studies used Mini-Mental State Examination as the primary cognitive function assessment, showing that glycemic control significantly delayed the degree of decline in cognitive function assessment scores (SMD=0.18; 95% CI 0.03, 0.34; p=0.02). Similar results were seen in two studies using the Montreal Cognitive Assessment scale, but without significant difference (SMD=0.05; 95% CI -0.10, 0.21; p=0.51). One study using Auditory Word Learning Test (AVLT) showed that glycemic control significantly delayed the decline in cognitive function assessment scores (SMD=0.52; 95% CI 0.11,0.93; p=0.01), and another used Wechsler Memory Scale Revised, showing similar results (SMD=1.45; 95% CI 0.86, 2.04; p<0.00001). Likewise, a study that used Modified Mini-Mental State scale showed that glycemic control significantly delayed the decline in cognitive function assessment scores (SMD=-0.10; 95% CI -0.16, -0.03; p=0.005). Lastly, one study used AVLT subtests to show that glycemic control delayed the decline in cognitive function assessment scores, although not statistically significant (SMD=0.09; 95% CI -0.53, 0.71; p=0.78). Conclusion: Glycemic control through antidiabetic treatment correlates with the improvement of cognitive impairment in patients with DM, hyperglycemia or insulin resistance. However, further studies are needed to validate the results of this study.